Seopyeonje : the southerners' song - Yi, Ch'ŏng-jun (Peter Owen, 2011)
A "song man" blinds his daughter to keep her from following her half-brother, who ran away due to the art's rigorous training. The girl forgives her father before his death, and through this act, she deepens her insight into the nature of human existence, and, as her father had insisted would happen, elevates the art of her p'ansori singing.